Effect of long term heat stress and dietary restriction on the expression of small heat shock protein (shsp) genes in rat liver tissue - Faruk Bozkaya; Mehmet Osman Atli; Aydın Guzeloglu; Seyit Ali Kayis; Mehmet Salih Kaya; Nurettin Aydilek (Eurasian Journal of Veterinary Sciences)
Aim: Investigation of the effects of dietary restriction on expression of certain small heat shock protein (sHSP) genes at mRNA level in liver tissue of rats reared under long-term heat stress. Material and Method: Sprague-Dawley rats (n=24) 10 weeks of age, were equally divided into four groups. Group I and II were kept at an ambient temperature of 22°C, while Groups III and IV were reared at 38°C. Groups I and III were fed ad libitum, while Groups II and IV were fed 60% of the diet consumed by their ad libitum counterparts. The treatment continued for 9 weeks. At the end of the treatment, liver tissue samples were taken. Total RNA was isolated and mRNA expression level of the HspB1, HspB2, HspB5, HspB6, HspB8, Hsp10, Hsp11 and HspA1A genes were assessed by Real-Time PCR analysis. Results: Heat stress significantly up regulated mRNA expressions of HspB2, HspB8 and Hsp70 genes, while it did not change mRNA expressions of HspB1, HspB5, HspB6, Hsp10 and Hsp11 genes. Dietary restriction (DR) did not significantly affect the expression of HspB1, HspB2, HspB8 HspB10, HspB11 and Hsp70, while it increased mRNA expression of HspB6 gene. No interaction between treatments was observed. Conclusions: The results suggested that long term heat stress differentially affected the sHSP genes studied and DR had no affect on the heat stress mediated changes in the expression of sHSP.